2018
DOI: 10.3382/ps/pey096
|View full text |Cite
|
Sign up to set email alerts
|

Performance, meat quality, and pectoral myopathies of broilers fed either corn or sorghum based diets supplemented with guanidinoacetic acid

Abstract: One experiment was conducted to evaluate the effects of guanidinoacetic acid (GAA) supplementation in broilers fed corn or sorghum-based diets on live performance, carcass and cut up yields, meat quality, and pectoral myopathies. The treatments consisted of corn or sorghum-based diets with or without the addition of GAA (600 g/ton). A total of 800 one-d-old male Ross 708 broiler chicks were randomly placed in 40 floor pens with 10 replicates (20 birds per pen) per each of the four treatments. At hatch, 14, 35,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 58 publications
4
44
1
2
Order By: Relevance
“…Supplementing 1,200 mg/kg GAA has been shown to improved feed conversion of broilers (Degroot, ; Majdeddin, Golian, Kermanshahi, Smet, & Michiels, ; Michiels et al, ). In further study, supplementation with 600 mg/kg GAA to broiler diets also improved average daily gain (ADG) and feed conversion (Córdova‐Noboa, Oviedo‐Rondón, Sarsour, Barnes, Ferzola et al, ; Heger et al, ; Metwally, Ibrahim, & Khater, ; Pradeep, Radermacher, & Girish, ). And the European Union authorized GAA as a feed additive for chickens for fattening at 600–1,200 mg/kg (EFSA, ).…”
Section: Introductionmentioning
confidence: 93%
“…Supplementing 1,200 mg/kg GAA has been shown to improved feed conversion of broilers (Degroot, ; Majdeddin, Golian, Kermanshahi, Smet, & Michiels, ; Michiels et al, ). In further study, supplementation with 600 mg/kg GAA to broiler diets also improved average daily gain (ADG) and feed conversion (Córdova‐Noboa, Oviedo‐Rondón, Sarsour, Barnes, Ferzola et al, ; Heger et al, ; Metwally, Ibrahim, & Khater, ; Pradeep, Radermacher, & Girish, ). And the European Union authorized GAA as a feed additive for chickens for fattening at 600–1,200 mg/kg (EFSA, ).…”
Section: Introductionmentioning
confidence: 93%
“…Analogously, different coccidiosis control approaches (Dalle Zotte, Tasoniero, Russo, Longoni, & Cecchinato, ) and dietary supplementation with antioxidants (vitamin E, C, and selenium) and organic trace minerals (Kuttappan et al., ; Sihvo et al., ; Sirri et al., ), which overall have been supposed to reduce muscle fiber oxidative stress associated with breast abnormality progress, did not result in any true mitigation effects. On the other hand, a slight reduction of moderate cases of WB has been obtained by dietary supplementation of guanidinoacetic acid used a precursor of creatine, but strong interaction with diet composition was found (Cordoba‐Noboa et al., ,b). Recently, it was demonstrated that an increase of arginine:lysine ratio can have a mitigation effect on breast meat abnormalities (Zampiga, Soglia, Petracci, Meluzzi, & Sirri, ) though a similar study led to a divergent outcome (Bodle et al., ).…”
Section: Means Of Alleviation: Facts and Challengesmentioning
confidence: 99%
“…Ibrahim et al (2019) also indicated that a possible shortage of methyl groups could be induced by long-term GAA supplementation in ducks, which could impair protein synthesis unless more methionine is added to the feed. In diets based on sorghum, the lower Arg, and Met digestibility as a consequence of kafirin and tannin presence could reduce the efficacy of GAA (Córdova-Noboa et al, 2018a). Therefore, attention to dietary factors seems essential, and more research is warranted to validate positive results with GAA.…”
Section: Parametermentioning
confidence: 99%
“…Generally, the reduction in the severity of myopathies has been associated with growth rate reduction ( Petracci et al, 2015 , 2019 ; Aviagen, 2019 ). Recent studies have reported that the dietary inclusion of guanidino acetic acid (GAA) partially ameliorated the occurrence and severity of WB myopathy while maintaining or improving live performance and breast meat yield ( Córdova-Noboa et al, 2018a , b ; Aviagen, 2019 ; Vargas, 2019 ). GAA is a metabolite precursor of creatine, a central energy molecule in muscles.…”
Section: Introductionmentioning
confidence: 99%